Analisis Pengaruh Arus Kas Bebas, Struktur Modal, Dan Investment Opportunity Set Terhadap Kebijakan Dividen - Taniel, Levi; Tjakrawala, Kurniawan (Jurnal Paradigma Akuntansi, 2024)
The purpose of this research is to know effect of free cash flow, modal structure, Investment Opportunity Set on dividend policy based on annual financial reports that have been prepared by manufacturing companies listed on the Indonesia Stock Exchange. In this study, the population was obtained using purposive sampling method in manufacturing companies listed on the. which are listed on the IDX with the category of manufacturing companies having financial statement data for the 2015-2019 period. Based on the sample research method, the obtained companies are 14. The analysis in this study uses the multiple linear regression analysis method using the SPSS Version 21 and Microsoft Excel 2016 . This study proves that free cash flow has a significant positive effect on dividend policy, modal structure has a significant negative effect on dividend policy, and Investment Opportunity Set has a significant negative effect on dividend policy